Exploring the non-linear impact of information and communication technology, globalization, and geopolitical risks on poverty in Pakistan - Nabila Khurshid; Nabila Akram; Mudassar Rashid (Research in Globalization)
The discussion around globalization often overlooks historical context and real-world dynamics, especially in the context of global development. This study examines the relationship between information and communication technology (ICT), geopolitical risks (GPR), and globalization in Pakistan from 1980 to 2022, with a focus on their impact on poverty. Using the Non-linear Autoregressive Distributive Lag (NARDL) model, the findings reveal that improvements in ICT infrastructure (ICT_POS) significantly reduce poverty, while setbacks in ICT (ICT_NEG) have minimal impact. On the other hand, rising geopolitical risks (GPR_POS) worsen poverty by reducing economic activity, investment, and trade, with negative geopolitical events (GPR_NEG) further exacerbating the issue. Positive economic globalization (EGB_POS) also plays a key role in reducing poverty, while the effects of negative globalization (EGB_NEG) remain unclear. The study recommends enhancing ICT infrastructure and accessibility, particularly in poverty-stricken regions, and addressing geopolitical risks through political stability and conflict resolution. These measures are essential for promoting economic growth and reducing poverty.